Depositional process and astronomical forcing model of lacustrine fine-grained sedimentary rocks: A case study of the early Paleogene in the Dongying Sag, Bohai Bay Basin. (March 2020) - Shi, Juye; Jin, Zhijun; Liu, Quanyou; Huang, Zhenkai
Abstract: The Paleogene strata of the Bohai Bay Basin include multiple sets of lacustrine fine-grained sediments, which provide a detailed record of the climate changes that occurred in the lake basin. Early Paleogene fine-grained sedimentary rocks are the main target layers of continental shale oil exploration in eastern China. Therefore, studies of the geological responses to astronomical factors have important theoretical and practical significance for understanding the depositional process of lacustrine fine-grained sedimentary rocks. In this paper, we focus on the lower Es3 (Es3l)-upper Es4 (Es4u) units in four shale oil wells in the Dongying Sag of the Bohai Bay Basin. Based on the previous establishment of a high-resolution astronomical time scale in this area, we have further studied the petrological characteristics and lithofacies of the fine-grained sedimentary rocks. Then the geological responses to astronomical cycles on different scales are investigated, and the models for the depositional process of fine-grained sedimentary rocks under the control of astronomical factors are revealed. The results indicate that the cyclic changes in mineral content and lithofacies in fine-grained sedimentary rocks in the Dongying Sag are controlled by short eccentricity and precession cycles. Periods near the maximum short eccentricity range had large precession amplitudes, humid climates, and the development of organic-rich laminated calcareous mudstone lithofacies. In contrast, periods near the minimum short eccentricity range had small precession amplitudes, a dry climates, and the development of organic-containing layered muddy limestone lithofacies. This study explores the depositional process of fine-grained sedimentary rocks from the perspective of astronomical cycles, which is conducive to the comprehensive prediction of favorable shale oil layers. Graphical abstract: Image 1 Highlights: High-resolution geochemical and sedimentary record of orbital cyclicity in Bohai Bay Basin. The depositional process of lacustrine fine-grained sedimentary rocks is mainly affected by eccentricity and precession. Two depositional models of lacustrine fine-grained sediments controlled by astronomical factors were established.